Effect of exogenous galectin-1 on leukocyte migration: Modulation of cytokine levels and adhesion molecules - Gil, Cristiane D.; Gullo, Caio E.; Oliani, Sonia M. [UNESP] (My University, 2011)
The effect of exogenous Gal-1 on cellular response and adhesion molecule expression was investigated in a classical model of acute inflammation induced by zymosan. C57BL6 mice, treated or not with human recombinant (hr) Gal-1, received i.p. injection of zymosan and peritoneal exudate, blood and mesentery were processed for cellular, biochemical, light and electron microscopic analysis after 4 and 24 h. Zymosan peritonitis provoked the expected signs of inflammation at 4 h, including a significant increase in extravasated PMNs in the mesentery and peritoneal exudate, mirrored by blood neutrophilia. These changes subsided after 24 h. Ultrastructural immunocytochemical analysis of PMNs showed significant Gal-1 expression and co-localization with L-selectin and β2-integrin in the plasma membrane and cytoplasm. Pharmacological treatment with hrGal-1 at 4 h produced an inhibition of PMN migration, associated with diminished expression of adhesion molecules, particularly β2-integrin, and TNF-α and IL-1β release by peritoneal cells. At 24 h, Gal-1 induced an increase in mononuclear phagocytic cell recruitment. In conclusion, our data propose an important mechanism of anti-inflammatory action of Gal-1, initially by modulation of proinflammatory cytokine release and PMN migration through an imbalance between adhesion molecule expression and, later, by promoting monocyte-macrophage recruitment.
Keywords: CD11b; CD62L; Immunocytochemistry; Monocyte; Neutrophil; Zymosan peritonitis